2008
DOI: 10.1111/j.1365-2656.2008.01342.x
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and space use: intraspecific and interspecific comparisons of movements and home ranges of two Colubrid snakes

Abstract: Summary 1.Energy requirements explain substantial variation in movement and home range size among birds and mammals. This study assesses whether the same is true of snakes by comparing ratsnakes ( Elaphe obsoleta ) and racers ( Coluber constrictor ), ecologically similar species whose energy requirements appear to differ substantially (racers > ratsnakes). 2. Over 4 years 22 Elaphe and 16 Coluber were radio-tracked at the same site in Illinois to examine how movement and home ranges varied by sex and season. 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 61 publications
5
35
0
Order By: Relevance
“…The maximum distance traveled by individuals in our study was up to 10 times farther than documented for populations further south (Hirth et al 1969, Brown and Parker 1976, Plummer and Congdon 1994, 1 exception: Moriarty and Linck 1997). In addition, home range sizes estimated for racers near the core of their range using similar MCP methods ranged from 1% to 17% the size of those in our study (Brown and Parker 1976, Plummer and Congdon 1994, Carfagno and Weatherhead 2008). Similarly, home range sizes of more southerly populations of Pituophis catenifer ranged from 2% to 39% the size of home ranges estimated for the bullsnakes we studied in Saskatchewan (Rodríguez‐Robles 2003, Kapfer et al 2008).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The maximum distance traveled by individuals in our study was up to 10 times farther than documented for populations further south (Hirth et al 1969, Brown and Parker 1976, Plummer and Congdon 1994, 1 exception: Moriarty and Linck 1997). In addition, home range sizes estimated for racers near the core of their range using similar MCP methods ranged from 1% to 17% the size of those in our study (Brown and Parker 1976, Plummer and Congdon 1994, Carfagno and Weatherhead 2008). Similarly, home range sizes of more southerly populations of Pituophis catenifer ranged from 2% to 39% the size of home ranges estimated for the bullsnakes we studied in Saskatchewan (Rodríguez‐Robles 2003, Kapfer et al 2008).…”
Section: Discussionsupporting
confidence: 49%
“…Larger home ranges have previously been recorded in northern populations of other snake species. For instance in Elaphe obsoleta obsoleta , home ranges were 3–4 times larger at the northern limit of their distribution compared to the core of their range in Illinois (Weatherhead and Hoysak 1989, Blouin‐Demers and Weatherhead 2002, Carfagno and Weatherhead 2008). This trend indicates that northern populations of snakes, especially those threatened with extinction because of human activities, likely need more protected land than their southern counterparts to accommodate their larger home ranges and longer movements.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, an increase in movement activity can be expected in the search for these resources [41]; however, these HR relocations can be energetically less demanding than the resources use itself [49]. Similarly, intensive movement does not always imply a large HR for an individual [50]. The aquatic environment allows fish to move with minimal energy expenditures; however, energy expenditures rapidly increases during active movement [33].…”
Section: Discussionmentioning
confidence: 99%
“…In tropical Australia, however, weather related variables within a season explained little variation in snake activity patterns and feeding rates (Brown and Shine 2002). Studies of the thermal ecology of snakes using telemetry have revealed much about the factors that affect their encounter rates with nests in North America (Carfagno and Weatherhead 2006, 2008). We believe that similar studies of predator activity (snakes or otherwise) in tropical habitats offer opportunities to further understand temporal, spatial, and interspecific variation in rates of nest predation on birds.…”
Section: Discussionmentioning
confidence: 99%